Study on drying characteristics of Gentiana macrophylla under the interaction of temperature and relative humidity. (15th June 2023) - Xing, Tianyu; Luo, Xi; Li, Ming; Wang, Yunfeng; Deng, Zhihan; Yao, Muchi; Zhang, Wenxiang; Zhang, Zude; Gao, Meng
Abstract: The heat and mass transfer as well as drying characteristics are influenced by temperature and relative humidity. The quality obtained after drying can be improved and the energy consumption can be reduced through reasonable modifications of the drying methods. Herein, 2000 kg Gentiana macrophylla was used to study changes in temperature and relative humidity during unsteady drying. The variation law and model of drying characteristics in unsteady drying are given. The moisture inhomogeneity, energy consumption and quality under different drying methods were analysed, and the drying methods were optimised. Results show that the relative humidity of the drying medium is greater than 60% during unsteady drying, hindering an increase in the drying temperature. Furthermore, the drying characteristic curve of the material lags during the drying process. The Weibull model could accurately predict the dehydration process in the unsteady drying of Gentiana macrophylla (R 2 = 0.9833). Moreover, we proposed a new three-stage variable-parameter drying method in which the temperature and relative humidity can be simultaneously changed. The proposed method can reduce energy consumption by 10.29% based on the comparison of the energy utilisation and processing results. Highlights: Temperature and relative humidity interact with one another. The drying method affects the color of the material. The method used to dry the material has an impact on its quality.